Brand management research in family firms: A structured review and suggestions for further research. Issue 3 (10th October 2016) - Beck, Susanne
Abstract : Purpose: The purpose of this paper is to highlight the relevance of conducting brand management research in a family firm context and to identify future research directions by reviewing and structuring the existing literature. Design/methodology/approach: The potential consequences of being a family firm on internal organizational processes and stakeholders' external perception are depicted. Afterwards the literature considering brand management research in family firms is reviewed systematically ( n =41) and structured by applying the Organizational Viewpoint Framework. Relevant research questions are derived based on the findings and their practical relevance is tested. Findings: The contributions are threefold. First, depicting the effects of being a family firm on the organization and its stakeholders highlights the relevance of conducting brand management research in family firms. Second, structuring the literature regarding the effects of being a family firm on organizational identity, intended brand image, construed brand image, and reputation helps derive research questions of theoretical and practical relevance that will serve the field as a guide for future research directions. Third, by extending the Organizational Viewpoint Framework originating from brand management research with the element of being a family firm, a further attempt at bridging both research fields is undertaken. Originality/value: This paper represents an important next step in the development of this research field by highlighting the importance of conducting brand management research in a family firm context and by structuring existent research to depict future research opportunities with theoretical and practical relevance.